Cannabis masks diabetic ketoacidosis. (7th October 2011) - Hennessy, Annemarie
Abstract : This is the first series to identify that diabetic ketosis presenting in cannabis users has a different and conflicting acid base profile compared to non-cannabis users and can confuse the need for intensive or critical care in these at-risk patients. This association of drugtaking history and clinical presentation has implications for how the authors treat the drug using sector of the population with diabetes.